End‐ischemic reconditioning of liver allografts: Controlling the rewarming. Issue 9 (September 2016) - Hoyer, Dieter Paul; Paul, Andreas; Luer, Sebastian; Reis, Henning; Efferz, Patrik; Minor, Thomas
Abstract : Different nonhypothermic preservation modalities have shown beneficial effects in liver transplantation models. This study compares controlled oxygenated rewarming (COR) to normothermic machine perfusion (NMP) to resuscitate liver grafts following cold storage (CS). Porcine livers were preserved for 18 hours by CS. Before reperfusion, the grafts were put on a machine perfusion device (Liver Assist) for 3 hours and were randomly assigned to COR (n = 6) or NMP (n = 5) and compared to standard CS. COR was carried out with the new Custodiol‐N solution, slowly increasing temperature from 8 °C to 20 °C during the first 90 minutes. NMP was carried out with diluted autologous blood at 37 °C for 3 hours. In both cases, the perfusate was oxygenated to partial pressure of oxygen > 500 mm Hg. Then liver viability was tested for 180 minutes during in vitro isolated sanguineous reperfusion. Activity of the mitochondrial caspase 9 was lower after COR. Measurement of tissue adenosine triphosphate and total adenine nucleotides at the end of the reconditioning period showed better energetic recovery after COR. COR also resulted in significantly lower enzyme leakage and higher bile production ( P  < 0.05) during reperfusion. This first comparison of COR and NMP as end‐ischemic reconditioning modalities demonstrates superior results in terms of mitochondrial integrity resulting in better energetic recovery, less hepatocellular injury, and ultimately superior function in favor of COR. Liver Transplantation 22 1223–1230 2016 AASLD